1993
DOI: 10.1159/000282534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shock Waves on the Male Reproductive System

Abstract: Although many reports concerning the effects of shock waves on the human body have been published, their effects on the male reproductive system are not well known. This report examines the effects of shock waves on human spermatozoa and rat testes. Semen samples were placed in water at 37 °C and 100, 200, 500, and 1,000 shock waves were applied. In proportion to an increasing number of shock waves, sperm motility and the percentage of viable sperm decreased, while the percentage of short-tailed sperm increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Although clinical and experimental investigations have suggested the safety of SWL, its possible effects on the male reproductive system are still not known. Furthermore, the literature contains a limited body of research with contradictory results on the possible effects of SWL on semen characteristic and gonads (10,11,(14)(15)(16)(17)(18)(19). Although Puppo et al (16) reported no adverse effect on male fertility, Andreessen et al (10) noted macroscopic and microscopic hemospermia and decreased sperm motility and sperm density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical and experimental investigations have suggested the safety of SWL, its possible effects on the male reproductive system are still not known. Furthermore, the literature contains a limited body of research with contradictory results on the possible effects of SWL on semen characteristic and gonads (10,11,(14)(15)(16)(17)(18)(19). Although Puppo et al (16) reported no adverse effect on male fertility, Andreessen et al (10) noted macroscopic and microscopic hemospermia and decreased sperm motility and sperm density.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the effects of interruption of the organogenesis of germ cells caused by the teratogenic potential of high-energy shock waves in a number of systems, such as in vitro effects of human spermatozoa (18). Ohmori and Matsuda (15) and Bedir et al (17) noted that spermatozoa and testis were irreversibly injured with an increasing number of shock waves. However, Deng et al (19) and Basar et al (11) showed only temporary histologic changes in testicular tissue in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although ESWL has minimal complications, its potential male reproductive system effects are unknown. Also, there have been few studies of possible effects of ESWL on semen quality and gonads with contradictory results [1,[8][9]10].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the effects of disruption of the organogenesis of germ cells caused by the teratogenic potential of high-energy shock waves in a number of systems, such as in vitro effects of human spermatozoa [6]. Ohmori et al showed that spermatozoa and testis were irreversibly damaged with an increasing number of shock waves [8]. We think the permanent damage of sperm occur due to testes, seminal vesicles and other parts of reproductive system close to the area of shock wave effect in males with less ureteral stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation